DNp63 Is regulated by BMP4 signaling and Is required for early epidermal development in Xenopus - Tríbulo, Celeste (2012)
It has been established in several models that the p63 gene has an important role in the development of the epidermis and its derivatives. In Xenopus, only the DNp63 isoform of this gene has been cloned and its role during epidermal development remains unknown. In this work, we showed that DNp63 is expressed in the non-neural ectoderm since the gastrula stage and that it is regulated by the bone morphogenetic protein 4 (BMP4) signaling pathway. Our in vivo and in vitro experiments demonstrated that DNp63 is required in the earliest inductive steps of epidermal development. The overexpression of DNp63 caused an increase in epidermal markers with a suppression of neural induction while the blocking of DNp63 led to the opposite results. Finally, we found that DNp63 acts as an anti-apoptotic gene, regulating the transcription of some apoptotic and anti-apoptotic factors. Taken together, these results suggest that DNp63 is an essential gene in early epidermal speciﬁcation under the control of BMP4.